FINANCIAL RESOURCES AS A FACTOR INFLUENCING ADOPTION OF INNOVATIONS ALONG MANGO VALUE CHAINS IN MERU COUNTY, KENYA - Isaiah Gitonga Imaita (European Scientific Journal, ESJ, 2014)
The study has used a descriptive survey design. The study was carried out in Meru County. The study area was limited to the lower part of Meru County whose climatic condition is suitable for mangoes production. This study adopted a probability sampling method to select the respondents for the study. Out of 13,574 farmers, traders and exporters, 447 farmers, 12 traders and 2 exporters were randomly selected for interview. Secondary data used in the study was collected from the Ministry of Agriculture Offices while primary data was collected from the respondents using a structured questionnaire with both open and close ended questions. To ensure validity and reliability, the researcher pretested the questionnaire and supervised the data collection. In this study, both qualitative and quantitative data were used in the analysis. Quantitative data obtained from the field was analyzed using descriptive and inferential techniques. The descriptive techniques adopted were means and frequencies while the inferential technique used were regression and correlation to establish relationship between variables in the study and inferences made. Frequency tables and charts were used to present the findings. The study found out that there were financial constraints as a result of low income due to reduced mango prices and lack of financial support to farmers. The study also found out that although majority of the growers and traders were aware of new innovations, they had not adopted the innovations due to lack of financial resources. Chi-square results show that financial resource has a significant association with innovation in Mango value chain as shown by a value of 120.981 at (p≤0.001). The researcher concludes that with such a steady growth in yields and development in mango farming in Meru County, Kenyan mango supply chain appears to be promising, and especially, in the adoption of new innovations. However, there is need for the government to employ strategies that will see farmers get incentives on their farm produce as well as financial support from financial institutions; there is also need to train the growers on entrepreneurship.